Emergent masculinities : gendered power and social change in the Biafran Atlantic age - Mbah, Ndubueze L., 1985- (New African histories series., 2019)
"In Emergent Masculinities, Ndubueze L. Mbah argues that the Bight of Biafra region's Atlanticization-or the interaction between regional processes and Atlantic forces such as the slave trade, colonialism, and Christianization-between 1750 and 1920 transformed gender into the primary mode of social differentiation in the region. He incorporates over 250 oral narratives of men and women across a range of social roles and professions with material culture practices, performance traditions, slave ship data, colonial records, and more to reveal how Africans channeled the socioeconomic forces of the Atlantic world through their local ideologies and practices. The gendered struggles over the means of social reproduction conditioned the Bight of Biafra region's participation in Atlantic systems of production and exchange, and defined the demography of the region's forced diaspora. By looking at male and female constructions of masculinity and sexuality as major indexes of social change, Emergent Masculinities transforms our understanding of the role of gender in precolonial Africa and fills a major gap in our knowledge of a broader set of theoretical and comparative issues linked to the slave trade and the African diaspora"--